The Malaria Parasitology - Alballal, Dr. Abd El Rahim (Gezira Journal of Health Sciences, 2004)
The microorganisms causing malaria are commonly referred to as malaria parasites, Plasmodium. In 1808 Laveran discovered plasmodium in blood in Algeria. There are nearly 120 species of plasmodia; 22 found in primate hosts, 19 found in rodents and bats and 70 found in birds and repliles.